The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1016/j.cub.2005.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Bacteria Protect Wasp Larvae from Fungal Infestation

Abstract: As a result of a printing error in the March 8, 2005 issue of Current Biology, pp. 475-479, the data in Figure 2 in this paper were compromised. A reprinted figure appears below. Current Biology regrets the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
117
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(117 citation statements)
references
References 0 publications
0
117
0
Order By: Relevance
“…Symbiotic bacteria play important roles in protecting their insect hosts from various threats, including viruses [61,62], fungal pathogens [13,15,63], parasites [64] and predators [65,66], as well as abiotic hazards such as heat shock [67,68]. However, these protective effects can differ markedly within a single symbiont 'species' [5,11,15].…”
Section: Discussionmentioning
confidence: 99%
“…Symbiotic bacteria play important roles in protecting their insect hosts from various threats, including viruses [61,62], fungal pathogens [13,15,63], parasites [64] and predators [65,66], as well as abiotic hazards such as heat shock [67,68]. However, these protective effects can differ markedly within a single symbiont 'species' [5,11,15].…”
Section: Discussionmentioning
confidence: 99%
“…Symbioses with prokaryotes are considered to promote Eukaryote diversification (Brucker and Bordenstein, 2012), particularly in insects (Moya et al, 2008;Gil et al, 2010). Some bacterial symbionts provide novel ecological traits to their insect hosts, for example, defense against pathogens or parasitoids (Oliver et al, 2003;Kaltenpoth et al, 2005), enhanced stress tolerance (Russell and Moran, 2006) or nutrients (Douglas, 2009). Nutrient-providing symbionts are commonly found in hosts with restricted diets, for example, aphids feeding on phloem sap (Baumann, 2005), blood-feeding diptera (Wang et al, 2013) or grain weevils (Heddi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The European beewolf (Philanthus triangulum, Hymenoptera, Crabronidae) engages in a unique and highly specific symbiosis with bacteria of the genus Streptomyces (Kaltenpoth et al, 2005). Female beewolves construct nest burrows in sandy soil, hunt honeybees (Apis mellifera), paralyse them by stinging and provision one to five honeybees as larval food in each brood cell Strohm & Linsenmair, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Since conditions in the brood cells are humid and warm, there is a continuous threat that the female's investment could be destroyed due to fungal or bacterial infection of the provisions or the immature wasp (Strohm & Linsenmair, 2001). Recent studies have shown that symbiotic bacteria protect beewolf offspring against fungal infection at the cocoon stage (Kaltenpoth et al, 2005).…”
Section: Introductionmentioning
confidence: 99%